Good caring and vocabularies of motive among foster carers - Jennifer Doyle; Rose Melville (Journal of Comparative Research in Anthropology and Sociology, 2013)
Employing C. Wright Mills’ concept of vocabulary of motives, this article examines the motives and attitudes of people who volunteer to foster children with high support needs. Data is drawn from a larger qualitative study involving indepth interviewing of 23 carers. When asked why they had become foster carers participants produced conventional accounts of child-centred altruistic motives–an acceptable vocabulary of motives which satisfied institutional and cultural expectations regarding caregiving. However, closer examination of participants’ experiences and attitudes revealed the likelihood that economic motives were also factors in decisions to foster. It is argued that participants chose to exclude economic motives from their accounts so as to avoid the risk of being seen to be ‘doing it for the money’.